PERCEPCIÓN DEL ROL QUE DESEMPEÑAN LAS MUJERES EN PUESTOS A NIVEL DIRECTIVO DEL MERCADO LABORAL - de la Vega, Laura Estela Fischer; Sánchez, David Chávez (European Scientific Journal, ESJ, 2015)
Today, the role played by women occupying managerial positions in the workplace is limited by the existence of gender discrimination. Under this premise, and in order to know the perception of the activity of the female sex in this area, was conducted this descriptive study through a questionnaire to 1240 graduates professionals (as) of the Faculty Accounting and Administration of the National University of Mexico (UNAM). The results suggest changes in paradigm shift in terms of employment preference for males.